2020
DOI: 10.1177/2158244019898730
|View full text |Cite
|
Sign up to set email alerts
|

Religiosity as a Cultural Resource for Arab-Palestinian Women’s Coping with Cancer

Abstract: Drawing on the discourse analysis of 36 in-depth interviews, this qualitative study explores how Arab-Palestinian women cope with breast cancer and ascribe meaning to their illness within the local religious and traditional cultural context. In particular, the study shows that religious beliefs and practices help Arab-Palestinian women to handle emotional and psychological difficulties while perpetuating traditional cultural norms of concealment. Two main functions of religiosity as a coping resource are analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 36 publications
0
4
0
1
Order By: Relevance
“…For example, it encourages Muslim believers to accept the crisis and painful events as part of God’s wise plan and view crisis as a test from God to deepen one’s beliefs. On the other hand, it discourages people from “giving up on the mercy of God” and getting involved in self-harm activities (Almuhtaseb et al 2020 ).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…For example, it encourages Muslim believers to accept the crisis and painful events as part of God’s wise plan and view crisis as a test from God to deepen one’s beliefs. On the other hand, it discourages people from “giving up on the mercy of God” and getting involved in self-harm activities (Almuhtaseb et al 2020 ).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Identifying the psychological and cultural disparities engendered by family cultures and belief systems may account for contrasts in coping with cancer and cancer outcomes. It may also give healthcare practitioners better understanding of the perception of roles among older women as patients and caregivers in Muslim and Jewish societies [23], as well as guide them in using cultural and spiritual traditions as tools for change and empowerment.…”
Section: Discussionmentioning
confidence: 99%
“…(39) Patients with cancer may rely on religious issues as important adaptive resources due to the lethal nature of cancer. (40) The results of some studies have shown that patients' spiritual needs vary based on their religious beliefs; and patients without religious beliefs had lower levels of hope and well-being than patients with religious beliefs (41,42) Thus, future studies with designing different religious affiliations and ethnicity are suggested to better clinical judgment regarding the impacts of spiritual based interventions. More investigations patients' responses can help to better understand influence of spirituality and religious on patients and their needs throughout the trajectory of a cancer diagnosis, treatment, and transition to end of life.…”
Section: Discussionmentioning
confidence: 99%